The kids' multicultural art book : art & craft experiences from around the world - Michaels, Alexandra (Charlotte, Vt. : Williamson Pub., 1993)
Includes background information and instructions for more than 100 craft projects from African, Native American, Eskimo, Asian, and Hispanic cultures.
"A Williamson kids can! book."
Includes bibliographical references (p. 154) and index.
Keywords: Handicraft -- Juvenile literature; Folk art -- Juvenile literature; Ethnic art -- Juvenile literature; Folk art; Handicraft